Engagement in technology-enhanced interventions for children and adolescents: Current status and recommendations for moving forward. (June 2020) - Georgeson, A.R.; Highlander, April; Loiselle, Raelyn; Zachary, Chloe; Jones, Deborah J.
Abstract: Treatment engagement is a primary challenge to the effectiveness of evidence-based treatments for children and adolescents. One solution to this challenge is technology, which has been proposed as an enhancement to or replacement for standard clinic-based, therapist delivered services. This review summarizes the current state of the field regarding technology's promise to enhance engagement. A review of this literature suggests that although the focus of much theoretical consideration, as well as funding priorities, relatively little empirical research has been published on the role of technology as a vehicle to enhance engagement in particular. Moreover, lack of consistency in constructs, design, and measures make it difficult to draw useful comparisons across studies and, in turn, to determine if and what progress has been made toward more definitive conclusions. At this point in the literature, we can say only that we do not yet definitively know if technology does (or does not) enhance engagement in evidence-based treatments for children and adolescents. Recommendations are provided with the hope of more definitively assessing technology's capacity to improve engagement, including more studies explicitly designed to assess this research question, as well as greater consistency across studies in the measurement of and designs used to test engagement. Highlights: Many studies of technology-enhanced treatments did not set out to examine the impact of technology on treatment engagement. The concept of engagement is not well defined or consistently measured in studies featuring technology Study design is a limiting factor in our ability to determine whether technology-enhanced treatments increase engagement